Selected Dynamic Problems of the Face Packing Seal. (2016) - Martsynkowskyy, Volodymyr; Kundera, Czeslaw; Gudkov, Sergii
Abstract: This paper analyzes the statics and dynamics of face packing seals, in which one of the sealing rings is made of elastic sealant. The study involved analyzing the axial vibration of the flexible ring for two configurations of its housing in the seal and determining the frequency characteristics and the condition of maintaining face-to-face contact between the sealing rings with considerably different elastic properties subjected to two types of external excitations. The derived analytical relationships were verified using a calculation example for real operating conditions of face packing seal in the pump.